Ação da saliva de Lutzomyia longipalpis (Diptera, Psychodidae) sobre o sistema complemento de cães (Canis familiaris), galinhas (Gallus gallus) e cobaias (Cavia porcellus) - Antonio Ferreira Mendes de Sousa (2012)
Inhibitors of the complement system (CS) are commonly present in the saliva of haematophagous insects. Experimental evidence suggests that these inhibitors are involved in the protection of the midgut against injury by CS present in the ingested blood. Previous studies have shown that the saliva of the Phlebotomine sandfly Lutzomyia longipalpis (the main vector of American Visceral Leishmaniasis) inhibited the human CS. Our aim was to investigate whether L. longipalpis` saliva inhibit the classical and alternative pathways of the complement system from other animals such as dogs, chickens and Guinea pigs. Erythrocyte lysis assays and ELISA for C3b detection assays were performed with dogs, chickens and Guinea pigs sera in the presence of different concentrations of salivary gland extract at pH 7,4 and 8,15 (the vector´s intestinal pH right after the blood meal). Only with dog sera, these assays were also done in the presence of the recombinant protein LJM19, a salivary inhibitor of the human classical pathway. Our results show that sandfly saliva is capable of strongly inhibiting the haemolysis by the dogs and Guinea pigs classical pathway. This was seen at both pHs. The chickens classical pathway was inhibited very weakly. At pH 7,4 saliva was unable to downregulate haemolytic activity of the alternative pathway for all three species studied, but when the pH was increased to 8,15, the dogs alternative pathway was strongly inhibited. The ELISA tests results matched those seen in the erythrocyte lysis assays. The LJM19 protein significantly inhibited the dogs´ hemolysis activity and C3b deposition from classical pathway. In conclusion, L. longipalpis´ salivary inhibitors protect the intestinal epithelium against the mammalian complement system. They appear to be species-specific, acting on mammals CS, but not on avian CS.